Association between osteoporosis or osteopenia and taking antiplatelet agents in general US population of NHANES - Lv, Hao; Wang, Jiuxiang; Zhu, Yujun; Hu, Zhimu; Wang, Ziwen; Qiao, Mingzhu; Jiang, Ting (Frontiers in Endocrinology, 2022)
Background: Osteoporosis (OP) and osteopenia are common bone disorders in old age, and lots of patients suffering from OP or osteopenia need to take antiplatelet agents meanwhile to treat basic diseases. However, clinical data on the link between osteopenia or OP and antiplatelet agents are limited. Methods: Data in this study was collected and screened from the NHANES from 2013 to 2014 and 2017 to 2018. The variables were extracted from interviews and compared between OP or osteopenia participants and normal. The relationship between OP or osteopenia and taking antiplatelet drugs was analyzed by weighted multivariate logistic regression. Results: After excluding individuals who were not eligible and had invalid data, we finally identified 894 participants for inclusion in the study. We found a negative association between OP or osteopenia and taking antiplatelet agents(OR = 0.53; 95% CI, 0.33-0.84; P < 0.05). These results did not change on multiple imputations(OR = 0.32, 95% CI, 0.19-0.56; P <0.01). In the subgroup analyses, the associations were more significant in females(OR = 0.18, 95% CI, 0.05-0.62; P <0.05). Conclusion: This study demonstrated the association between OP or osteopenia and taking antiplatelet agents was significant. Therefore it’s necessary to confirm the result by extending further research.